Apps for Kids – A Question of Quality - Lensen, Fiona (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
Today, children in families have good access to mobile devices with touchscreens. In this context, numerous apps for learning, playing, reading or being creative can be used. However, the question of what is a good app cannot be answered easily. Since there was no list of criteria for the assessment of apps, yet, the Media Literacy Lab decided to engage with this topic in an open online course. During this course, both a first set of criteria as well as a website with reviews of more than 100 apps for children were built.